2020
DOI: 10.1007/s00330-020-07320-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of computed tomography texture analysis using dual-energy-based bone marrow imaging for multiple myeloma characterization: comparison with histology and established serologic parameters

Abstract: Objective To identify textural features on dual-energy CT (DECT)–based bone marrow images in myeloma which correlate with serum markers of myeloma activity and the degree of medullary involvement. Methods A total of 110 patients (63.0 ± 11.0 years, 51 female) who underwent unenhanced whole-body DECT between September 2015 and February 2019 were retrospectively included, which was approved by our institutional ethics committee with a waiver of the informed consent requirement. All patients had current hematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The peak at the left end of both histograms can be explained by the virtual calcium removal, which results in extreme negative attenuation of structures with dense calcification. Further, the large overlap of both histograms in the range of negative HU values might reflect the resemblance of bone mineral density of both subsets: after virtual calcium removal, the bone mineral density might crucially influence the negative part of the attenuation histogram A recent study correlated BM texture analysis in dualenergy CT (DECT) with BM infiltration in MM [34]. The study extracted 92 PyRadiomics features for each of 56 patients, which yielded six significant features for Pearson's correlation with BM infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at the left end of both histograms can be explained by the virtual calcium removal, which results in extreme negative attenuation of structures with dense calcification. Further, the large overlap of both histograms in the range of negative HU values might reflect the resemblance of bone mineral density of both subsets: after virtual calcium removal, the bone mineral density might crucially influence the negative part of the attenuation histogram A recent study correlated BM texture analysis in dualenergy CT (DECT) with BM infiltration in MM [34]. The study extracted 92 PyRadiomics features for each of 56 patients, which yielded six significant features for Pearson's correlation with BM infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate sample size of the multivariate regression was calculated by the software G*Power for a desired power level of 0.8, significance level of 0.05, and an estimated medium to large effect size (f 2 = 0.32) of the main Fig. 2 Inclusion chart of the study population independent variable, based on reported data (supplementary data 3) [34,35].…”
Section: Statistical Assessmentmentioning
confidence: 99%
“…Nonetheless, the potentially useful information of MRI has yet not been fully exploited. Several studies have shown some efficiency of the bone marrow radiomics, a study had revealed that dual-energy CT textural features correlate well with MM-related serologic parameters and histology ( 25 ). Another study confirmed the predictive value of radiomics based on PET-CT imaging in MM ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Texture analysis can quantify the intuitive quality described by terms such as roughness, smoothness, or bump as a function of spatial variation in pixel intensity. The heterogeneity of different results can be explored through texture analysis to identify texture features that can be used for diagnosis and prediction [ 27 ]. At present, texture analysis has been widely used in tumor imaging, has important value in the judgment of benign and malignant tumors, metastasis, and prognosis, and can guide clinical treatment.…”
Section: Discussionmentioning
confidence: 99%